Volitional Organization of Personality: Search for Relevant Diagnostic Indicators - Shamlyan, Karina (Psychological Prospects Journal, 2015)
Volitional personality organization is represented by a relatively wide range of qualities that are different in their nature and functions. The difficulties in the diagnosis of personal volitional organization are supposed to be the following: there are different classifications of volitional qualities; not all the qualities that belong to the volitional sphere meet the required characteristics of volitional regulation; some specific features of individual volitional qualities are insufficiently clearly delineated both at the level of theoretical determination by different authors, and at the level of empirical indicators. Our approach to the diagnosis is to focus the attention on certain difficulties and obstacles that a person faces, and also on volitional techniques that are used in order to overcome them in determining the empirical indicators of various volitional qualities. Unfortunately, at present there is a lack of research revealing the connections among primary elements of volitional regulation and permanent features of the person’s volitional activity – his volitional qualities. The aim of the study was to analyze some empirical indicators of readiness to overcome difficulties and obstacles, their connection with indicators of permanent features of volitional activity. We present the results of the empirical study that analyzed students’ attitude to the difficulties and obstacles they may encounter when performing academic tasks. The test group awareness degree of the need to complete the task in conditions hindered and the degree of their readiness to perform this task were volitional self-regulation indicators. The relationship between the indicators of volitional self-regulation and permanent features of volitional activity is analyzed. Some methods of descriptive statistics and also comparative and correlation analysis were applied for statistical data processing.